Music Perception Testing Reveals Advantages and Continued Challenges for Children Using Bilateral Cochlear Implants - Steel, Morrison M.; Polonenko, Melissa J.; Giannantonio, Sara; Hopyan, Talar; Papsin, Blake C.; Gordon, Karen A. (Frontiers in Psychology, 2020)
A modified version of the child’s Montreal Battery of Evaluation of Amusia (cMBEA) was used to assess music perception in children using bilateral cochlear implants. Our overall aim was to promote better performance by children with CIs on the cMBEA by modifying the complement of instruments used in the test and adding pieces transposed in frequency. The 10 test trials played by piano were removed and 2 high and 2 low frequency trials added to each of 5 subtests (20 additional). The modified cMBEA was completed by 14 children using bilateral cochlear implants and 23 peers with normal hearing. Results were compared with performance on the original version of the cMBEA previously reported in groups of similar aged children: 2 groups with normal hearing (n=23:Hopyan et al., 2012; n=16:Polonenko et al., 2017), 1 group using bilateral cochlear implants (CIs) (n=26:Polonenko et al., 2017), 1 group using bimodal (hearing aid and CI) devices (n=8:Polonenko et al., 2017), and 1 group using unilateral CI (n=23:Hopyan et al., 2012). Children with normal hearing had high scores on the modified version of the cMBEA and there were no significant score differences from children with normal hearing who completed the original cMBEA. Children with CIs showed no significant improvement in scores on the modified cMBEA compared to peers with CIs who completed the original version of the test. The group with bilateral CIs who completed the modified cMBEA showed a trend toward better abilities to remember music compared to children listening through a unilateral CI but effects were smaller than in previous cohorts of children with bilateral CIs and bimodal devices who completed the original cMBEA. Results confirmed that musical perception changes with the type of instrument and is better for music transposed to higher rather than lower frequencies for children with normal hearing but not for children using bilateral CIs. Overall, the modified version of the cMBEA revealed that modifications to music do not overcome the limitations of the CI to improve music perception for children.